Analisis Motivasi Belajar Perspektif QS. Al-Ra’d: 11 Dalam Kitab Tafsir al-Jalalain - Kurnia PS, Alaika M. Bagus; Yustika, Gaung Perwira (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2018)
In this research, the writer analyzes some learning motivations on the view of Al-Qur’an Chapter al-Ra’d : Verse 11 in the approach of Kitab Tafsir al Jalalain by Imam Jalaluddin al Mahalli and Imam Jalaluddin al-Suyuti. Based on many sources, the writer concludes that this verse elaborates three values of education : parents’ supervision and guidance becomes the first solution that can motivates students, complete facilities both in home or school becomes the second solution in term of designing the into passive motivators. The last is a reward or. Punishment. Keywords: Analysis, Motivation, Study.